54th AIAA Aerospace Sciences Meeting 2016
DOI: 10.2514/6.2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Active Flow Control Enhanced Vertical Tail Technology Development

Abstract: This paper summarizes a joint NASA/Boeing research effort to advance Active Flow Control (AFC) technology to enhance aerodynamic efficiency of a vertical tail. Sweeping jet AFC technology was successfully tested on subscale and full-scale models as well as in flight. The subscale test was performed at Caltech on a ~14% scale model. More than 50% side force enhancement was achieved by the sweeping jet actuation when the momentum coefficient was 1.7%. AFC caused significant increases in suction pressure on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…Andino et al 22 and Lin et al discussed actuator spacing results and reported that the trends are based on momentum coefficient. Lin et al 24 also discussed flight testing with AFC on the Boeing 757 ecoDemonstrator where the results indicated flow reattachment over the rudder and a smoother flight.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Andino et al 22 and Lin et al discussed actuator spacing results and reported that the trends are based on momentum coefficient. Lin et al 24 also discussed flight testing with AFC on the Boeing 757 ecoDemonstrator where the results indicated flow reattachment over the rudder and a smoother flight.…”
Section: Introductionmentioning
confidence: 95%
“…Their work included cases at flight Reynolds numbers. Full-scale experiments at flight Reynolds numbers were carried out by Andino et al 22 , Whalen et al 23 , and Lin et al 24 on a Boeing 757 vertical tail retrofit with sweeping jets. Results showed that the performance enhancement seen on subscale models exists on full-scale tails and that active flow control is a viable option for future aerospace usage.…”
Section: Introductionmentioning
confidence: 99%
“…The first drag reduction technology employed an array of pneumatic-based AFC devices called the sweeping jet actuators 5 (Figure 1) on the vertical tail of the Boeing 757 for side force enhancement (Figure 2). 6 These devices were of the same geometry and configuration that was successfully tested on a full-scale Boeing 757 vertical tail model in NASA Ames' National Full-Scale Aerodynamics Complex (NFAC) 40'x80' wind tunnel. 7,8 A NASA sponsored system integration study on a mid-sized twin aisle airplane indicated using AFC would allow designers to scale-down the vertical tail of a mid-sized twin aisle airplane and reduce aircraft drag by 0.4%, which would reduce fuel burn.…”
mentioning
confidence: 99%
“…The most obvious possibility, therefore, is to supply the HLAFC system with bleed air coming from either the main engines, or the APU, or both. In fact, recent flight test demonstrations that showcased AFC applied to the vertical tail used APU bleed air to supply the AFC actuators [6,7].…”
Section: Hlafc Architectures Consideredmentioning
confidence: 99%
“…The fundamental principle of AFC is to improve aircraft performance by modifying the airflow surrounding the vehicle through the addition of an acceptable amount of flow energy. Recent work in this field has included theoretical studies [1][2][3], experimental research [4,5], and some flight-test demonstrations [6,7].…”
Section: Introductionmentioning
confidence: 99%